Legel Problem Concerning Juristic Persons and Liability of Registered Ordinary Partnerships - suebroek, arunee; Arunee Suebroek (Law for Development Graduate Journal, 2024)
The purpose of this independent study is to study the status of juristic person and liability of partners. Once the ordinary partnership is registered, the partnership and its partners will be assigned of rights and duties by the law. However, the question is that, is the effect of the rights and duty assignment by the sufficient to protect or to serve as a risk-reducing tool for business owners. Therefore, I made a comparative study with the partnership law of United Kingdom, which could be considered a modern country with economic prosperity, to make an analysis for solution and appropriate revision for the law in Thailand. Regarding the study, the main point of the status of juristic person of ordinary partnership and the liability of the juristic ordinary partnership is the separation between the partnership and the juristic ordinary partnership. Still, the status of juristic person for an ordinary partnership and the partners could not be separated entirely since all the partners have the rights to manage the partnership and there is a collective consequence. Also, all the partners still have unlimited liabilities. This also shows that the partnership will have more obligations once registered but does not receive any benefit of being registered fully or equally with other registered business entities that have statuses of juristic person. According to the reasons above, I consider that there should be revisions on the status of a juristic person for ordinary partnership and a limit of liability of an ordinary partnership. I have 2 suggestions as follows; the first one is the registration for the ordinary partnership should be cancelled. Normally, the forming of the ordinary partnership does not require registration by the law. The law only allows the registration for ordinary partnership if preferred according to section 1064 1st paragraph. Once the registration happens, the ordinary partnership will become a juristic person. However, the law does not provide the limit of liability after becoming the juristic person despite the partnership with juristic status and the partners. However, when I looked at the liability, the partners still have unlimited liabilities after the registration of the ordinary partnership. As a result, the liability of the juristic ordinary partnership requires the liability provisions of ordinary partnership as a mutatis mutandis provisions. As a result, the registration of the ordinary partnership to transform it into the juristic ordinary partnership should be cancelled. My 2nd suggestion is that, regarding the liability, I suggested that Thailand should use the partnership law, Limited Liability Partnerships, of United Kingdom, as a model for improving the partnership law in Thailand. Based on the study, I saw the benefit and strength of Limited Liability Partnerships, which is called “First Fundamental Innovation in this Respect in this Century”. The main strength that distinguishes this ordinary partnership from other partnerships is (1) this ordinary partnership has its own characteristics as it allows the partners to enter the contract by themselves, using their own names, and (2) the limit of liability, a partner has limited liability, based on their capitals. In conclusion, I learnt about the benefit and the importance of such concept. I also wish to see the change in ordinary partnership law in Thailand to be more up-to-date and beneficial to the country. The law should be improved to be similar to other countries and to promote the investment while reducing the risks that the business owners must face. This will ultimately benefit Thailand as a whole.